Literasi Keuangan Mahasiswa Ditinjau dari Gender, Teman Sebaya, dan Pembelajaran Kewirausahaan - Dwi Luvita Sari; Pujiati Pujiati; Rahmah Dianti Putri (FKIP Universitas Lampung, 2020)
This study aims to determine the effect of gender, peers, and entrepreneurial learning, both partially and simultaneously, on Economics and Education Students' financial literacy at the University of Lampung in 2017 and 2018. The method used in this research is descriptive verification with ex post facto and survey approaches. The population in this study amounted to 129 students. The sample obtained was 56 students, and the sampling technique is nonprobability sampling using purposive sampling. The study results show: (1) There is a gender influence on the financial literacy of Economics and Education students at the University of Lampung in 2017 and 2018. (2) There is the influence of peers on the University of Lampung's financial literacy in 2017 and 2018 Economics Education students. (3) There is an influence of entrepreneurial learning on the financial literacy of Lampung University in 2017 and 2018 Economics Education students (4) There is the influence of gender, peers, and learning entrepreneurship simultaneously on the financial literacy of the 2017 and 2018 University of Lampung University Economic Education students.Keyword: Interest in Becoming a Teacher, Motivation to Become a Teacher, Perceptions of Students in Choosing FKIP, and Considerations of the Labor Market http://dx.doi.org/10.23960/E3J/v3i1.1-9